نظرية القدر وتأويلها عند موسى بن ميمون-منخلال دلالة الحائرين- - خديجة, صحرواي; رحمة, غضبان (جامعة الوادي university of eloued, 2020)
كانت ولازالت مسألة القضاء والقدر تمثل تساؤلا للإنسان على امتداد التاريخ البشري، فمسألة القضاء والقدر ليست مسألة تأملية بحثية بل واقعا معاشا ومشكلته تتعلق بالفعل والسلوك الإنساني ،فنرى أن الإنسان غير متقبلا لقضائه وقدره حتى وإن كان خيرا فما بالك إن كان شرا فهو يريد الأفضل دائما وهذه طبيعة النفس البشرية، فنأخذ نظرية واحد ا من أهم علماء اليهود على مدى التاريخ وهو " موسى بن ميمون الأندلسي " صاحب " دلالة الحائرين " الذي من خلال كتابه سنبين نظريته ،و الذي أعاد صياغة الفكر الديني اليهودي على أ سس كلامية وفلسفية متأثرة بالاتجاهات الكلامية والفلسفية الإسلامية أمثال" ابن رشد" و "أبي حامد الغزالي "وغيرهما. تأثر" موسى بن ميمون " بالديانة الإسلام والمسلمين جعله يأخذ هذه المسألة التي تعد ركنا من أركان الإيمان ووضع مثلها كذلك لأركان الإيمان اليهودي الثلاثة عشر الذي لا يوجد لها كتاب مخصص لبيانها وتفصيلها . نظرة " موسى بن ميمون " للقضاء والقدر هي نفس نظرة المتشرعين اليهود بالإضافة إلى نظرة جزئية من نظرة " أرسطو " لهذا الموضوع. فهو ينسب الخير إلى الله فكلما هو من عند الله هو خير محض، وأن كل الشرور إعدام حيث قسم الشرور إلى ثلاث: شر طبيعي ،شر إنساني متعدي، شر ذاتي من نفسه، حيث أن كل الشرور التي تصيب الإنسان هي ما أفتعلها بذاته جراء أغراضه و شهواته فكلها تأتي من جهله وعدم علمه بالله تعالى ،فإذا أطاع الله تعالى يصل إلى أعلى درجات الكمال الإنساني وهيا بالعبادة والصلاة وأتباع أوامر الله والابتعاد على نواهيه.وما يقره " موسى بن ميمون " من خلال تفسيره للكتاب المقدس أن أفعال الله مقدرة وذات مشيئة وأن كلما يصيب الإنسان له غرض وسبب ونحن نجهله بالإضافة أن الله ترك لنا الحرية في اختيار أفعالنا فه و عالم بكل شيء ومسير لهذا الكون و أفعالنا و أعمالنا فهي من اختيارنا وإرادتنا بأنفسنا إلا أنه على الإنسان أن يكون مؤمنا متقبلا لم ا يصيبه فأحيانا ما نمر به يكون امتحانا لصبرنا وقوة إيماننا بالله تعالى .The issue of judiciary and destiny was and still is a question for man throughout human history, for the issue of judiciary and destiny is not a contemplative and research issue but rather a reality of pension and its problem is related to the actual and human behavior, so we see that the human being is unacceptable to his judiciary and his destiny even if it is good then what if it is evil then he always wants the best This is the nature of the human psyche, so we take the theory of one of the most important Jewish scholars throughout history, which is “Musa bin Maimon Al-Andalusi”, the owner of “The Significance of the Confused” through which his book will show his theory through him, who reformulated Jewish religious thought on verbal and philosophical foundations influenced by verbal and philosophical trends Islamic examples such as "Ibn Rushd" and "Abu Hamid Al-Ghazali" and others. "Musa bin Maimon" was influenced by the religion of Islam and Muslims. He made him take this issue, which is one of the pillars of faith, and set similar examples to the thirteen pillars of the Jewish faith, for which there is no book dedicated to its statement and detail. "Musa bin Maimon"s view of fate and destiny is the same as that of Jewish lawmakers, in addition to a partial view of Aristotle's view of this issue. He attributes good toAllh(God), so everything that is fromAllh(God) is pure good, and that all evil is execution where he divided evil into three: natural evil, human transgressor evil, self-evil from himself, as all the evil that afflicts a person is what I do by himself due to his purposes His desires are all from his ignorance and his lack of knowledge ofAllh(God) Almighty. IfAllh(God) obeysAllh(God) Almighty, he will reach the highest levels of human perfection and come to worship and prayer and followAllh(God)’s orders and move away from his intentions. الملخص And what "Musa bin Maimon" approves through his interpretation of the Bible is that the actions ofAllh(God) are estimated and of the will and that everything that affects a person has a purpose and a reason and we do not know him. In addition,Allh(God) has left us freedom to choose our actions because he is aware of everything and walks of this universe except our actions and actions, it is of our choice and our will on our own, except that a person must be a believer who accepts what he afflicts, sometimes what we go through is an examination of our patience and the strength of our belief in Allh (God).
ليسانس
Keywords: القضاء, القدر, الإرادة, العناية الإلهية, الشر, الخير, الحرية, التخيير, التسيير, الأفعال ,الشريعة اليهودية; nation , destiny , will , care , evil , the good freedom. , choice , running , actions , flood